System pomiarowo-sterujący do sterowania modelem ciężarówki z rozpoznawaniem obrazu z kamery = The measurement and control system for truck model control with image recognition from the camera - Mróz, Piotr; Kujawa, Daniel (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
At the Institute of Metrology, Electronics and Computer Science, the research is underway to develop a measurement and control system supervising the work of four sets of tractor models with semi-trailers. The works are carried out in the direction of the tractor automatically approaching any semi-trailer. Therefore, the first step is to recognize the semi-trailer based on the camera image.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne